Disclosure of violence against women and girls in Senegal - Peterman, Amber; Dione, Malick; Le Port, Agnes; Briaux, Justine; Lamesse, Fatma; Hidrobo, Melissa (Oxford University Press, 2025)
Measures of violence against women and girls (VAWG) are widely collected in surveys, yet estimates are acknowledged to be lower bounds of the true prevalence. This study reports on a survey experiment randomly assigning 3,400 women and girls to either face-to-face interviews or audio computer-assisted self-interviews (ACASI), a modality that increases privacy and confidentiality of responses. Results show the ACASI group discloses higher prevalence of lifetime intimate partner violence by 4 to 7 percentage points compared to face-to-face interviews. Differences in disclosure for nonpartner VAWG are even larger, ranging from 6 to 12 percentage points. Tests for correlates of characteristics that might lead to increased disclosure show few notable patterns. Overall results suggest ACASI are a promising way to encourage disclosure, however trade-offs include limits in the complexity of questions that can be asked and higher time costs associated with development and implementation of surveys.